Development of MPLMSC (Maritime Port and Logistics Management Schedule Class) Mobile Web App to Facilitate MPLM Students in Accessing Course Schedules - Purnomo, Farasabila Angeli; Isha, Nabila Farraha; Sahara, Siti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Engineering at Universitas Negeri Jakarta, focusing on equipping students with specialized knowledge in managing maritime operations and logistics. Traditionally, MPLM students rely on the university's Academic Information System (SIAKAD) to access essential academic information, including course schedules and room assignments. However, the frequent changes in schedules due to various factors, such as faculty availability and special events, have highlighted the need for a more dynamic and responsive scheduling tool. This study addresses this need by developing a mobile web application specifically designed for class scheduling. The application aims to streamline the process by allowing students to easily access real-time schedule updates, including changes in the mode of delivery (whether online or offline). The research was conducted using the Research and Development method, following the 4D development model: define, design, develop, and disseminate. The evaluation of the application indicated a high level of user satisfaction, with a positive response rate of 86.76%, demonstrating its effectiveness in meeting the needs of both students and faculty.